ANALYSIS OF CONSUMER LEGAL PROTECTION AGAINST UNFAIR CLAUSES IN SMART CONTRACTS IN INDONESIA - Girsang, Fredsly Hendra Sardol; Sijabat, Candra Robasa; Rahmadanti, Siti Mutiah (Universitas Dharmawangsa, 2025)
The swift advancement of blockchain technology has introduced a transformative innovation known as smart contracts, which are self-enforcing, unchangeable computer programs for agreements. While these contracts offer benefits like efficiency and openness, their inherent qualities present major hurdles for protecting consumers, especially from the risk of inequitable terms being included. This study aims to deeply investigate the strengths and weaknesses of current Indonesian law in offering legal safeguards to consumers who use smart contracts for their transactions. Utilizing a normative juridical methodology with a statutory and conceptual framework, the research reveals several key findings. First, the essential features of smart contracts, most notably their unchangeable and self-enforcing nature, are in direct opposition to the adaptable and justice-focused principles of Indonesian contract law, like the doctrine of good faith. Second, although a foundational level of protection is offered by the Indonesian Civil Code (KUHPerdata), the Consumer Protection Law (UUPK), and the Law on Information and Electronic Transactions (UU ITE), substantial legal vacuums and difficult enforcement problems persist. Third, the research pinpoints specific ways unfair clauses appear as functions within the code and confirms that applying a purposeful interpretation of current legislation can help lessen their negative effects. In conclusion, this paper asserts the pressing requirement for creating specific legal rules and bolstering institutional supervision, especially by the Financial Services Authority (OJK), to ensure that consumer rights remain protected amidst the evolution of contractual technology.